The Influence of Tax Knowledge, Taxpayer Awareness on MSME Taxpayer Compliance in Cileungsi District - Wicaksono, Daniar Puspita; Mulyani, Sri; Rahmaniar, Ani (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study aims to examine the influence of tax knowledge and taxpayer awareness on the compliance of taxpayers of MSME actors in Cileungsi District. The object of this research is Individual Taxpayers who run businesses that are included in the category of Micro, Small, and Medium Enterprises (MSMEs) and are registered at KPP Pratama Cileungsi. The population in this study is 711 micro, small and medium entrepreneurs, the sample in this study is 88 respondents. Hypothesis testing uses multiple regression analysis. Data analysis using spss version 26. The results of this study are (1) The results of this study show that tax knowledge has a positive influence on the compliance of MSME taxpayers in the region, (2) The results of this study show that Taxpayer Awareness has a positive influence on the compliance of MSME taxpayers in Cileungsi District. And the results of the hypothesis test show that the significant level of F has a value less than α or that the Fcount is greater than the Ftable. It can be concluded that tax knowledge and awareness of tax payment obligations have a significant influence on the compliance of MSME taxpayers in Cileungsi District.